Odpowiedzialność karna za pozakodeksowe przestępstwa gospodarcze: Criminal responsibility for economic crimes of outside statutory - Przychodzień, Justyna (Management and Administration Journal, 2021)
Economic crime as a phenomenon rightly regarded as a social problem with a complex and multi-faceted character. The common feature of these crimes is acting against a specific victim and at the same time reconciling the widely understood complex economic interests of the state. Economic crimes compounded by negative macroeconomic effects and leads to the impoverishment of entire population groups Combating pathology focus of media attention, public prosecutor's offices and the judiciary, specialized and the general public. The effectiveness of prosecution of economic crime and criminal policy chosen are the basic criteria for evaluating the activities of law enforcement and justice. The purpose of this article is to present selected aspects of criminal liability for outside statutory of economic crimes and to determine the legal consequences of a breach of the provisions of the criminal law business.